Method of Appraising Economic Prospects of Mining Exploration over Large Territories: Algerian Sahara Case Study - Allais, M. (Management Science, 1957)
The present study has essentially been conceived as a part of a larger study in the field of operations research. Its purpose resides in the scientific detection of the best and economically optimal strategy to be used in prospecting for metal deposits in the Sahara. The purpose of mining exploration is to discover workable deposits, and to acquire certain information on the natural wealth. This, of course, will involve certain costs. With zero expenditure there is zero information. But the cost of complete information would be inconceivable. Between these two extremes there is an optimum which we propose to seek. Obviously, the determination of such optimum is impossible unless a certain attitude towards risk is adopted. Such determination will also be conditional on at least an approximate knowledge of the probability distributions involved in the problem. The present study aims at the analysis of the second aspect, and attempts to evaluate the economic prospects of mining exploration in the Sahara, from the point of view of statistical distributions of both the number of deposits and their value.